Assessment of the Validity of the Sinonasal Outcomes Test‐22 in Pituitary Surgery: A Multicenter Prospective Trial. (1st July 2021) - Sarris, Christina E.; Little, Andrew S.; Kshettry, Varun R.; Rosen, Marc R.; Rehl, Ryan M.; Haegen, Timothy W.; Rabinowitz, Mindy R.; Nyquist, Gurston G.; Recinos, Pablo F.; Sindwani, Raj; Woodard, Troy D.; Farrell, Christopher J.; et al.
Abstract : Objectives/Hypothesis: Sinonasal Outcomes Test‐22 (SNOT‐22) is used widely as a patient‐reported sinonasal quality‐of‐life (QOL) instrument for endoscopic endonasal pituitary surgery. However, it has never been validated in this population. This study explores the psychometric validity of SNOT‐22 to determine if it is a valid scale in patients undergoing endoscopic pituitary surgery. Study Design: Multicenter prospective trial. Methods: Adult patients (n = 113) with pituitary tumors undergoing endoscopic surgery were enrolled in a multicenter study. Patient‐reported QOL was assessed using SNOT‐22 and the Anterior Skull Base Nasal Inventory‐12. Face validity, internal consistency, responsiveness to clinical change, test–retest reliability, and concurrent validity were determined using standard statistical methods. Results: Internal consistency using Cronbach's alpha at baseline and 2 weeks postoperatively were 0.911 and 0.922, indicating SNOT‐22 performed well as a single construct. Mean QOL scores were significantly worse at 2 weeks than baseline (16.4 ± 15.1 vs. 23.1 ± 16.4, P  < .001), indicating the scale is responsive to clinical change. However, only 11/22 items demonstrated significant changes in mean scores at 2 weeks. Correlation between scores at 2 and 3 weeks was high, suggesting good test–retest reliability, r (107) = 0.75, P  < .001. Factor analysis suggests the five‐factor solution proposed for the SNOT‐22 in rhinosinusitis patients is not valid in pituitary surgery patients. Conclusions: The SNOT‐22 is a valid QOL instrument in patients undergoing endoscopic pituitary surgery. However, because it includes 22 items, can be applied only as a single construct, 50% of the items do not demonstrate changes after surgery, and is not as sensitive to change as other scales, shorter instruments developed specifically for this patient population may be preferable. Level of Evidence: 2 Laryngoscope, 131:E2757–E2763, 2021